Identification of Student Learning Styles based on Multiple Intelligences Aspects using the Dempster-Shafer Method - Hidayat, Julkarnain; Putri, Raissa Amanda (Sistemasi: Jurnal Sistem Informasi, 2024)
Learning style refers to an individual's process of understanding and absorbing information, which is influenced by sensory preferences, problem-solving strategies, and communication styles. This research explains the learning styles of high school students by utilizing the theory of multiple intelligences, identifying seven aspects: visual, auditory, kinesthetic, verbal-linguistic, logical-mathematical, social-interpersonal, and solitary-intrapersonal. With a better understanding of students' learning styles, teachers can devise more effective teaching methods, improving learning outcomes. This research aims to apply the Dempster-Shafer method in an expert system to identify the learning styles of high school students, especially in SMA Swasta Dharmawangsa Medan. Through interviews with guidance teachers and questionnaires from grade X students, the expert system will provide information and customized learning methods, improving teacher understanding and student participation. With PHP-based web technology, the system is designed to simplify the process and provide a user-friendly interface and efficient data management, in the hope of creating a more productive and supportive learning environment.